2019
DOI: 10.1038/s41598-019-47404-0
|View full text |Cite
|
Sign up to set email alerts
|

Rational drug-design approach supported with thermodynamic studies — a peptide leader for the efficient bi-substrate inhibitor of protein kinase CK2

Abstract: Numerous inhibitors of protein kinases act on the basis of competition, targeting the ATP binding site. In this work, we present a procedure of rational design of a bi-substrate inhibitor, complemented with biophysical assays. The inhibitors of this type are commonly engineered by combining ligands carrying an ATP-like part with a peptide or peptide-mimicking fragment that determines specificity. Approach presented in this paper led to generation of a specific system for independent screening for efficient lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The low- and high-concentration asymptotes were fitted individually for each experiment. All calculations were performed using the appropriate model [ 32 , 33 ] implemented in Origin 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The low- and high-concentration asymptotes were fitted individually for each experiment. All calculations were performed using the appropriate model [ 32 , 33 ] implemented in Origin 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibitory effect was monitored for all studied compounds using the previously described method, 43 based on the luminescence measured with the SpectraMax iD3 Multi‐Mode Microplate Reader (Molecular Devices). Inhibitor concentration varied in the range of 1 nM–1 mM; however, for some compounds with a limited solubility the maximal concentration tested was lower.…”
Section: Methodsmentioning
confidence: 99%
“…70 In 2019, Winiewska-Szajewska et al identified a 6-mer peptide (KESEEE-NH 2 ) which weakly binds to the CK2α substrate binding-site (K d = 0.39 mM). 71 They showed that both the peptide and the ATP-competitive inhibitor TBI could bind simultaneously to CK2 without a drastic loss in binding affinity (K d = 0.45 mM for KESEEE-NH 2 with TBI present). 71 Therefore, the novel peptide KESEEE-NH 2 represents a potential substrate-competitive inhibitor.…”
Section: Substrate Channel Inhibitorsmentioning
confidence: 99%
“…71 They showed that both the peptide and the ATP-competitive inhibitor TBI could bind simultaneously to CK2 without a drastic loss in binding affinity (K d = 0.45 mM for KESEEE-NH 2 with TBI present). 71 Therefore, the novel peptide KESEEE-NH 2 represents a potential substrate-competitive inhibitor.…”
Section: Substrate Channel Inhibitorsmentioning
confidence: 99%